Obročkanje vpijatov (Coraciiformes) v okviru slovenske obročkovalske sheme - Vrezec, Al (Scopolia, 2017)
The Slovenian Bird Ringing Scheme was established in 1927 and has been continuously maintained until today, when it is run by the Slovenian Bird Ringing Center, which operates within the framework of the Slovenian Natural History Museum. This paper deals with the data on the ringing of three species of Coraciiformes as an example of a migration atlas for selected species from the territory of Slovenia. The fewest ringing data (N = 6) were collected for the European Roller (Coracias garrulus). In 2014, a pair bred in Slovenia, but the birds were part of the Austrian population and were marked according to the Austrian colour ring scheme. The most commonly ringed species of Coraciiformes in Slovenia was the Common Kingfisher (Alcedo atthis) (N = 4,110 ringed birds). They were mostly ringed after 1987, especially during the autumn migration period between August and October. The longest recovery of the Kingfisher is from Estonia (1,614 km), with the oldest specimen at least 2 years and 11 months old. In general, birds from Central and Eastern Europe occur during migration and are wintering in Slovenia. According to biometric data, only the subspecies A. a. ispida occurs in Slovenia. The lowest values of the condition index were achieved in the postbreeding dispersion and during the autumn migration between August and October, while the highest values were found in the winter period in December. Reducing the mass is therefore most critical in the summer and autumn months, when greater effects on the population and the survival of birds could also be expected. Most European Bee-eaters (Merops apiaster) in Slovenia were ringed after 2002 between June and September. A migratory pathway of Bee-eaters breeding in Germany runs across Slovenia, from which three finds from some 700 km distant breeding population in Saxony have already been recorded.
Keywords: Alcedo atthis; biometrija; biometry; bird ringing; birds; Coracias garrulus; Coraciiformes; finds; Merops apiaster; najdbe; obročkanje ptic; ornitologija; Ptiči; recoveries; Slovenia; Slovenija; vpijati